IMPROVING ANTIBIOTIC PRESCRIBING PATTERN AND ASSESSMENT OF CO-MORBIDITIES ASSOCIATED WITH RESPIRATORY TRACT INFECTIONS - K., Shyama; R., Prudence A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The objective of this study was to describe the antibiotic prescribing pattern and co-morbidities associated with lower respiratory tract infections by means of cross-observational study. Methods: A cross-sectional, open labelled and observational study was undertaken in a multi-speciality hospital for a period of 9 mo (November 2013-July2014). Lower respiratory tract infected patients who satisfied the selection criteria were included in the study. They were followed clinically and biochemically in the study. Results: During the study period, most predominant antibiotics used were cephalosporin's which constitute about 63 % (with 3rd generation being the highest). Hypertension was found to be the most frequent co-morbidity (43%). Route of administration for most of the patients was parenteral followed by tablets and a very few on capsules. A few were changed from parenteral to oral when they met with the clinical criteria's for switching over therapy. Conclusion: This study describes the antibiotic prescribing pattern and co-morbidities associated with lower respiratory tract infected patients.